A Study on Expressions of Politeness Strategies in Barack Obama's 27 Greatest Speeches Introduced in the Book "We Are the Change We Seek: The Speeches of Brack Obama" - Xa Thi Thu Hien
Chapter 1. Rationale ...; Chapter 2. Literature review...3. Methodology...; ...